A Pragmatic Study of the Abuse of Language in Orwell’s Novel: Nineteen Eighty-Four. - Abdul- Hussein Turkey , Tabarak; Jasim Al- Hilu, Mazin (Journal of College of Education, 2020)
This research is concerned with analysing pragmatically the abuse of language upon people. The analysis focuses on the British novel, “Nineteen Eighty-Four” by George Orwell. This study aims at analysing the language used in the novel and showing how it can be used as an oppressive device that can be abused to lead to a totalitarian state. The model of analysis that is used in the current study is Grice’s theory of implicature and the cooperative principles (1975). The researcher employs qualitative method to have deep understanding and examination to the data of the present study. The results of this research reveal that pragmatic analysis shows that language can be used as a tool to spread power and authority. It can lead to a whole totalitarianism when those in power imply their aims and intuitions in the words they use. The implied meaning occurs when the speaker does not use the language directly and violates the relevance, the manner, the quality and the quantity maxims and being uncooperative. The study also shows the role and power that the language has upon the thought and behaviour of people.
Keywords: Keywords: Power, ideology. pragmatics, Grice’s Theory of Implicature and Cooperative Principle.